Native DIGE proteomic analysis of mitochondria from substantia nigra and striatum during neuronal degeneration and its compensation in an animal model of early Parkinson's disease. (19th October 2016) - Kuter, Katarzyna; Kratochwil, Manuela; Marx, Sven-Hendric; Hartwig, Sonja; Lehr, Stephan; Sugawa, Michiru D.; Dencher, Norbert A.
Abstract: Cause of Parkinson's disease (PD) is still not understood. Motor symptoms are not observed at early stages of disease due to compensatory processes. Dysfunction of mitochondria was indicated already at preclinical PD. Selective toxin 6-OHDA was applied to kill dopaminergic neurons in substantia nigra and disturb neuronal transmission in striatum. Early phase of active degeneration and later stage, when surviving cells adapted to function normally, were analysed. 2D BN/SDS difference gel electrophoresis (DIGE) of mitochondrial proteome enabled to point out crucial processes involved at both time-points in dopaminergic structures. Marker proteins such as DPYSL2, HSP60, ATP1A3, EAAT2 indicated structural remodelling, cytoskeleton rearrangement, organelle trafficking, axon outgrowth and regeneration. Adaptations in dopaminergic and glutamatergic neurotransmission, recycling of synaptic vesicles, along with enlargement of mitochondria mass were proposed as causative for compensation. Changed expression of carbohydrates metabolism and oxidative phosphorylation proteins were described, including their protein–protein interactions and supercomplex assembly.